Dissolution behaviour of radiocaesium-bearing microparticles released from the Fukushima nuclear plant - Okumura, Taiga (Sci Rep, 2019)
Radiocaesium-bearing microparticles (CsMPs) composed of silicate glass were released by the Fukushima Daiichi Nuclear Power Plant accident in March 2011. Since CsMPs contain a high concentration of radiocaesium, their dynamics and fate in the environment are urgent issues to be investigated. Here, we show that CsMPs are dissolved by weathering in the environment and that their radioactivity is more rapidly decreased by dissolution than the physical decay of radiocaesium. We conducted dissolution experiments with CsMPs in pure water that absorbed CO(2) from the atmosphere and in artificial seawater at several temperatures. The dissolution progress was monitored by the decrease in the (137)Cs radioactivity in CsMPs, and the dissolution rate was estimated. The activation energy for the dissolution of CsMPs was estimated to be 65 and 88 kJ/mol and the dissolution rate at 13 °C (approximate annual mean temperature in Fukushima City) was 0.014 and 0.140 μm/y for pure water and seawater, respectively, assuming that radiocaesium is uniformly distributed in spherical CsMPs. The shapes of the CsMPs dissolved in pure water were considerably altered, suggesting that the dissolution proceeded without maintaining the geometry. Tin oxide and iron oxide nanoparticulates formed on the surfaces. Such features were similar to those observed in CsMPs recently collected in Fukushima Prefecture, indicating that weathering dissolution of CsMPs is also occurring in the environment. For the CsMPs dissolved in seawater, a crust of secondary Mg- and Fe-rich minerals was formed, and the glass matrix inside the crust decreased, creating space between the crust and the glass matrix.